Rat dental pulp stem cells: isolation and phenotypic characterization method aiming bone tissue bioengineering - Bruno Machado Bertassoli (Brazilian Archives of Biology and Technology)
ABSTRACT: Dental pulp stem cells (DPSC) have been showing a considerable potential for regenerative medicine. Pulps were collected from lower incisors (n=2) through direct access of the tooth pulp chamber. The isolated cells were cultured in alfa-MEM 10% FBS, in standard culture conditions. At the third passage, DPSC were characterized by flow cytometry (MHCI, CD54, CD73, CD90, CD45, CD11 and CD34); RT-PCR for Nanog gene; and their differentiation capacity in osteogenic, adipogenic and chondrogenic cell lines. Isolated cells exhibited adhesion capacity to plastic; fusiform morphology, and 80% confluence reached in approximately 3 days. These cells have also revealed positive expression for CD54, CD73 and CD90 markers; and negative expression for CD11, CD34 and CD45. Nanog expression was detected by RT-PCR, expected for a mesenchymal stem cell profile. DPSC chondrogenic differentiation was confirmed by positive staining in Alcian Blue; lipidic droplets stained with oil red confirmed their capacity to differentiate in adipogenic fate; while mineralized beads, stained with alizarin red, confirmed their differentiation in osteogenic phenotype. These results indicate the viability of the isolation and expansion of rat DPSC following this method, and osteogenic differentiation potential opens new perspectives for in vivo studies and the use of these cells in cellular therapies and tissue bioengineering, aiming bone repair.